2011
DOI: 10.1111/j.1365-2966.2011.19276.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay times and rates for Type Ia supernovae and thermonuclear explosions from double-detonation sub-Chandrasekhar mass models

Abstract: We present theoretical delay times and rates of thermonuclear explosions that are thought to produce Type Ia supernovae (SNe Ia), including the double‐detonation sub‐Chandrasekhar mass model, using the population synthesis binary evolution code startrack. If detonations of sub‐Chandrasekhar mass carbon–oxygen white dwarfs following a detonation in an accumulated layer of helium on the white dwarf’s surface (‘double‐detonation’ models) are able to produce thermonuclear explosions which are characteristically si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
200
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(215 citation statements)
references
References 96 publications
13
200
1
1
Order By: Relevance
“…Maoz et al (2011) study the hosts of the local SNe found in the LOSS and find a prompt channel (with τ < 420 Myr) with 99% significance. Models of Ia explosions also show the possibility of such a channel (Nomoto et al 2009;Ruiter et al 2011). The Ia rates are then modelled with one prompt component, directly proportional to the SFH, and one delayed component.…”
Section: Delay Time Distributions For Ia Supernovaementioning
confidence: 99%
“…Maoz et al (2011) study the hosts of the local SNe found in the LOSS and find a prompt channel (with τ < 420 Myr) with 99% significance. Models of Ia explosions also show the possibility of such a channel (Nomoto et al 2009;Ruiter et al 2011). The Ia rates are then modelled with one prompt component, directly proportional to the SFH, and one delayed component.…”
Section: Delay Time Distributions For Ia Supernovaementioning
confidence: 99%
“…Most of these discussions above focused on the Chandrasekhar mass model, in which the WDs explode as SNe Ia when their masses are close to the Chandrasekhar mass limit. However, the sub-Chandrasekhar mass model may still be able to explain SNe Ia such as 1991bg, as well as normal SNe Ia (Sim et al 2010;Ruiter et al 2011). In addition, observations of several very bright SNe Ia implied that their progenitor WDs might have a super-Chandrasekhar mass (Astier et al 2006;Howell et al 2006;Hicken et al 2007;Scalzo et al 2010;Yuan et al 2010;Tanaka et al 2010;Yamanaka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in the observational instruments and methods, the properties of low-mass companions (q0.3) around earlytype stars at intermediate orbital periods (P≈50-10 4 days) remain elusive. This region is especially interesting because low-mass X-ray binaries and millisecond pulsars that form in the galactic field (Kalogera & Webbink 1998;Kiel & Hurley 2006), as well as certain channels of Type Ia supernovae (Whelan & Iben 1973;Ruiter et al 2011), may evolve from extreme mass-ratio binaries at initially intermediate orbital periods (Figure 1). Although we investigate all portions of the binary parameter space, we are especially concerned with determining accurate companion statistics at intermediate orbital periods.…”
Section: Introductionmentioning
confidence: 99%